New Measures to Protect the Adult. Challenges for Lawyers and Forensic Doctors - Lucaciuc, Ștefan; Crișan, Corina (Journal of Legal Studies, 2023)
A decision of the Constitutional Court, which declared the unconstitutionality of art. 164 of the Civil Code, which regulated the protection measure of placing under interdiction, offered the lawmaker the opportunity to rethink the protection measures of the natural person that involve restricting or increasing one’s capacity of exercise. The new regulation proposed by Law no. 140/2022 brings with it both protection measures to which people with intellectual or psychosocial disabilities can appeal in the conventional means - legal aid and the warrant of protection - as well as protection measures for people who are found to have a deterioration of the mental faculties – legal advice and special guardianship - the establishment of which is given to the competence of the court with the amendment that the court is free to choose the measure of protection that best corresponds to the vulnerable person’s concrete needs, being able to configure its content so that the measure of protection to be adequate to the circumstances in which the person finds oneself and the restriction of own freedom to be proportional to the severity of the effects that this deterioration of the mental faculties of the vulnerable person causes to that person’s psychological abilities.